A STUDY ON ILLOCUTIONARY ACTS USED BY THE MAIN CHARACTER OF SPIDER-MAN : FAR FROM HOME MOVIE - Riko April Liyawan; Wiwin Indiarti; Yuli Sugianto (LUNAR, 2022)
This research is a descriptive qualitative which analyze the illocutionary act in the main character in Spider-Man: Far From Home Movie. This research aimed to identify the types and functions of illocutionary act in the main character in Spider-Man: Far From Home Movie. The researcher used Miles and Hubberman’s theory to analyze the data. It consists of data reduction, data display, and conclusion drawing/verification. The research found that there are 4 types of illocutionary act that used by the main character in Spider-Man: Far From Home Movie based on Searle theory: those are representatives, expressives, directives, and commisives. Directive is the most illocutionary act used in this Movie. They appeared 36 times. It is followed by expressives which are uttered 31 times. Then, representatives are uttered 8 times and commisives are uttered 3 times. Therefore, There are 4 types of illocutionary function used in this movie based on Searle theory: competitive, convivial, collaborative, and conflictive. Competitive is the most illocutionary function used in this movie. They appeared 55 time. It is followed by convivial which are uttered 16 times. Then, collaborative uttered 4 times. The forth is conflictive that uttered one times.